Implementation of Self-Acceptance in the PukPuk Station Mental Health Community Support Group through Group Communication - Sabrina, Eya Rusydasani; Suminar, Jenny Ratna; Damayanti, Trie (Informasi, 2024)
This research aims to explore the implementation of self-acceptance in support group in the PukPuk Station mental health community through a group communication approach. It has relation that mental health is an important variable in improving individual well-being and health. The research method used was qualitative with a phenomenological design. Data was collected through participant observation, in-depth interviews with group members, and document analysis of group meeting notes. This research uses some theory concept such as group communication, mental health, self-acceptance. Research findings show that through structured and open group communication, support group members are able to increase their level of self-acceptance. Factors such as social support, mutual identification, and social learning also play an important role in the process of self-acceptance. The open, deep, and structured communication creates a safe environment for members to strengthen their self-acceptance. Then, about the practical of this research are importance of strengthening group communication skills in the training and development of support group members, as well as expanding access to community programs that emphasize the importance of self-acceptance. The implication of this research is the importance of strengthening group communication in supporting individual self-acceptance processes in the context of the mental health community Keywords: self-acceptance, support group, group communication